Scaling SRE organizations : the journey from 1 to many teams (O'Reilly Media, 2019)
"A lot has been said about the SRE profession (how to start an SRE team, how to scale a single team in place, etc.), but how to move from a single SRE team to an SRE organization that requires several teams has been largely unexplored. Gustavo Franco (Google) takes new SRE leaders and individual contributors through what it takes to be a part of or start their second team and beyond. Join in to learn from his experience starting new teams and splitting and moving them from both technical and nontechnical standpoints. This session was recorded at the 2019 O'Reilly Velocity Conference in San Jose."--Resource description page